Role of Chitosan Application in Postoperative Abdominal Adhesions in Rabbits: S.I. Salih1; E’atelaf A. Al-Mutheffer1; A.K. Mahdi1; R.A, S. Al-Naimi2 - Al-Mutheffer, E’atelaf A. (The Iraqi Journal of Veterinary Medicine, 2015)
This study was performed to evaluate the reliability and efficacy of intra-peritoneal performances of chitosan powder in preventing abdominal adhesions following laparotomy. Twenty clinically healthy rabbits of both sexes, weighing 1.5-2 kg were allocated randomly into 2 equal groups; control group (G1) and treated group (G2). After surgical preparation the animals had undergone to laparotomy which was performed to create a sero-muscular incision of 4cm length in the stomach, in G1 the incision was closed by suturing stomach wound and abdominal wall, While (G2) animals were subjected to same operation but after stomach incision suturing, 1gr. of chitosan powder was sprinkled on stomach incision and peritoneal cavity prior to the lina alba and skin closures. 5 animals of each group were euthanized at two periods: 7th and 21st day post operation, adhesions in abdominal cavity were examined macroscopically and microscopically. The results showed clearly no adhesions at the operation site (the stomach wound), also on all abdominal organs and peritoneum cavity in both examination periods in G2. In conclusion this study revealed that chitosan plays a vital role in restrictions of intra-abdominal adhesion even though the mechanism of action is still unknown.